Liability and Narrowly Targeted Wars - Gunasekera, Crystal Allen (Ethical theory and moral practice, 2016)
Targeted killings have traditionally been viewed as a dirty tactic, even within war. However, I argue that just combatants actually have a prima facie duty to use targeted strikes against military and political leadership rather than conventional methods of fighting. This is because the leaders of a military engaging in aggression are typically responsible for the wrongful harms they threaten, whereas significant numbers of their solders usually will not be. Conventional warfare imposes significant risks on soldiers who are not liable to be killed, violating their rights. Narrowly targeted strikes frequently provide a less-wrongful alternative. Consequently, there is a prima facie duty to conduct such strikes, and to exercise due care if engagement with conventional forces becomes necessary.